The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep20125
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Nucleation of both Ge-Fresnoite and Benitoite/BaGe4O9 during the Surface Crystallisation of Glass Studied by Electron Backscatter Diffraction

Abstract: Two glasses of the compositions 2 BaO - TiO2 - 2.75 GeO2 and 2 BaO – TiO2 –3.67 GeO2 (also known as BTG55) are annealed at temperatures from 680 to 970 °C to induce surface crystallization. The resulting samples are analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM) including electron backscatter diffraction (EBSD). Ge-Fresnoite (Ba2TiGe2O8, BTG) is observed at the immediate surface of all samples and oriented nucleation is proven in both compositions. After a very fast kinetic selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…20°. Considering this tilt, it can be concluded that the microstructure in Figure features Ba-fresnoite dendrites growing perpendicular to the surface, similar to the observations made for BT0.75G in a related glass-ceramic . Bulk nucleation was not detected in this BT3S glass-ceramics after the applied heat treatment.…”
Section: Results and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…20°. Considering this tilt, it can be concluded that the microstructure in Figure features Ba-fresnoite dendrites growing perpendicular to the surface, similar to the observations made for BT0.75G in a related glass-ceramic . Bulk nucleation was not detected in this BT3S glass-ceramics after the applied heat treatment.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Figure presents an SEM micrograph obtained from a cross section of the BT0.75S glass-ceramic showing an area where the growth fronts from the top and right side of the sample collided. In analogy to Ge-fresnoite, Ba-fresnoite shows no growth front interaction. Hence, the dendritic crystals growing in the BT0.75S-glass at 810 °C simply collide and prevent each other from further growth, similar to the observations made for Ge-fresnoite …”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4 indicate an oriented nucleation of ε-YS with the c-axis preferably parallel to the surface and of Y-ZrO 2 with a {111}-plane parallel to the surface. Oriented nucleation has currently been detected in more than five glass systems, most recently in Ge-fresnoite 43 where multiple phases showed up to three orientation preferences at the immediate surface after crystallization 43 . As the ε-YS dendrites in the EBSD-scan of Fig.…”
Section: Discussionmentioning
confidence: 99%